Circulating miRNAs are associated with sleep duration in children/adolescents: Results of the I.Family Study. Issue 2 (8th January 2020) - Iacomino, Giuseppe; Lauria, Fabio; Russo, Paola; Marena, Pasquale; Venezia, Antonella; Iannaccone, Nunzia; De Henauw, Stefaan; Foraita, Ronja; Heidinger‐Felső, Regina; Hunsberger, Monica; Kourides, Yiannis; Moreno, Luis A; et al.
Abstract : New Findings: What is the central question of this study? Are differential patterns of circulating miRNAs associated with sleep duration in normal‐weight European children and adolescents? What is the main finding and its importance? Differences in the expression level of circulating miR‐26b‐3p and miR‐485‐5p are positively associated with total sleep duration in healthy normal‐weight children and adolescents. Abstract: It is commonly recognized that sleep is essential for children's health, and that insufficient sleep duration is associated with negative health outcomes. In humans, sleep duration and quality are influenced by genetic, environmental and social factors. Epigenetic mechanisms, likewise, regulate circadian rhythms and sleep patterns. In the present study, we aimed to identify circulating microRNAs associated with sleep duration in a subsample of normal‐weight European children/adolescents ( n  = 111) participating in the I.Family Study. Subjects were divided into two groups based upon self‐reported sleep duration, according to the recommended amount of sleep for paediatric populations. Sleep needs for children <13 years were at least 9 h per day, and for children >13 were at least 8 h per day. There were group differences (short sleepers versus normal sleepers) in circulating levels of miR‐26b‐3p (mean (95% CI) = 2.0 (1.3–2.7) versus 2.3 (1.9–2.7), P  = 0.05) and miR‐485‐5p (mean (95% CI) = 0.6 (0.3–0.9) versus 0.9 (0.7 – 1.0), P  < 0.001), adjusting for country of origin, age, sex, pubertal status, screen time and highest educational level of parents. Our findings show for the first time that sleep duration reflects the profile of specific circulating microRNAs in school‐aged children and adolescents. It is conceivable that epigenetic modifications, mainly related to circadian rhythm control, may be modulated or interfere with sleep duration. Abstract :